META-ANALISIS PENGARUH MODEL-MODEL PEMBELAJARAN FISIKA DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA PADA MATERI FISIKA - Zurhaimi, Tri Zeni Adha; Mufit, Fatni (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2021)
In today's world of education, students are required to think critically. Therefore, a learning process is needed that can improve students' critical thinking skills, one of which is in choosing a learning model. The chosen learning model certainly has its advantages and disadvantages. So in this study aims to analyze or compare several studies that have been conducted related to the most influential learning model to improve students' critical thinking skills. The model in this study is a meta-analysis. From the results of the analysis of the highest effect size value based on the learning model, namely the guided discovery learning model, namely 1.13 with a very high category. The highest effect size value based on educational level, namely at the tertiary education level, 1.19 is in the very high category. And the effect size value is based on the learning material used, namely environmental physics material, 1.19, very high category.